2014
DOI: 10.1007/s11053-014-9255-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genetic Algorithm (GA) in History Matching of the Vapour Extraction (VAPEX) Heavy Oil Recovery Process

Abstract: This paper presents the application of genetic algorithm (GA) to the history-matching problem. As history matching of VAPEX (vapour extraction) experiments is a complex, highly nonlinear, and non-unique inverse problem, a modified GA was developed to assist the history-matching process. Compared to conventional GA, the computational time in this modified GA approach was reduced by 71 %, and an excellent match between the simulation data and experimental data was achieved, with the error being less than 1 %. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…When applied to a waterflood they found that their approach gave comparable results to a full adjoint based method. Xu et al [78] applied a modified GA for the history matching of a Vapor Extraction (VAPEX) heavy oil recovery process. They found that their modified approach increased computational efficiency while achieving an excellent match.…”
Section: History Matching As Precursor To Production Optimizationmentioning
confidence: 99%
“…When applied to a waterflood they found that their approach gave comparable results to a full adjoint based method. Xu et al [78] applied a modified GA for the history matching of a Vapor Extraction (VAPEX) heavy oil recovery process. They found that their modified approach increased computational efficiency while achieving an excellent match.…”
Section: History Matching As Precursor To Production Optimizationmentioning
confidence: 99%